PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) PADA MATERI LAJU REAKSI (JS (JURNAL SEKOLAH), 2022)
Abstract : Development of Student Worksheets (LKPD) Based on STEM (Science, Technology, Engineering, And Mathematics) on Reaction Rate Material. This study aims to determine the level of validity, practicality, and student responses to STEM-based student worksheets on the reaction rate material. This development research uses a 4-D development model consisting of 4 stages, namely, 1) Definition, 2) Design, 3) Development, 4) Dissemination. The subjects in this study were 2 material expert validators, 2 media expert validators, 2 chemistry teachers, and 25 students of class XI IPA 1, totaling 25 students. The data collection instruments were in the form of interview guidelines, LKPD validation sheets by validators, practicality questionnaire sheets by teachers, and student response questionnaire sheets using data analysis techniques using quantitative and qualitative data. Based on the results of the study, the average assessment by material experts was 78.5% in the appropriate category, the assessment by media experts was 91% in the very appropriate category, the average practicality level assessment by the teacher was 97.7% in the very practical category, and the results of student responses, namely 98.8% of students who gave "yes" answers and 1.2% of students who gave "no" answers so that the LKPD developed was in the good category. Keywords : LKPD, STEM, Reaction Rate, 4-D Model Abstrak : Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis STEM (Science, Technology, Engineering, And Mathematics) Pada Materi Laju Reaksi. Penelitian  ini bertujuan untuk mengetahui tingkat kevalidan, praktikalitas, dan respon peserta didik terhadap lembar kerja peserta didik berbasis STEM pada materi laju reaksi. Penelitian pengembangan ini menggunakan model pengembangan 4-D yang terdiri atas 4 tahap yaitu, 1) Pendefinisian (Define), 2) Perancangan (Design), 3) Pengembangan (Develop), 4) Penyebaran (Disseminate). Adapun subjek pada penelitian ini yaitu 2 orang validator ahli materi, 2 orang validator ahli media, 2 orang guru kimia, dan siswa kelas XI IPA 1 yang berjumlah 25 siswa. Instrumen pengumpulan data berupa pedoman wawancara, lembar validasi LKPD oleh validator, lembar angket praktikalitas oleh guru, dan lembar angket respon peserta didik dengan teknik analisis data menggunakan data kuantitatif dan kualitatif. Berdasarkan hasil penelitian diperoleh rata-rata penilaian oleh ahli materi sebesar 78,5% dengan kategori layak, penilaian oleh ahli media sebesar 91% dengan kategori sangat layak, rata-rata penilaian tingkat kepraktisan oleh guru sebesar 97,7% dengan kategori sangat praktis, dan hasil respon peserta didik yaitu 98,8% siswa yang memberi jawaban œiya dan 1,2% siswa yang memberi jawaban œtidak sehingga LKPD yang dikembangkan berada pada kategori baik. Kata Kunci : LKPD, STEM, Laju Reaksi, Model 4-D